Carbon free SiO2–SO3H supported Pt bifunctional electrocatalyst for unitized regenerative fuel cells. (7th December 2016) - Roh, Sung-Hee; Sadhasivam, T.; Kim, Hansung; Park, Jeong-Hun; Jung, Ho-Young
Abstract: The electrochemical performance of sulfonated silica-supported Pt electrocatalyst investigated as a bifunctional oxygen electrode for unitized regenerative fuel cell (URFC) system. The measured electrochemical surface area values are 23.02 and 22.96 m 2 g −1 for the Pt black and 80 wt% Pt/SiO2 –SO3 H catalysts, respectively. The silica support is not prohibiting the electrical conductivity of Pt in the Pt/SiO2 –SO3 H electrocatalyst due to the high loading of Pt on the supporter. The oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in the fuel cell and water electrolyzer modes were carried out in a unit cell for the Pt/C, Pt/SiO2, and Pt/SiO2 –SO3 H electrocatalysts. The Pt/SiO2 –SO3 H catalyst is exhibit better performance in oxygen reduction (hydrogen oxidation) and oxygen evolution (hydrogen evolution) reactions during cyclic processing due to the high proton conductivity of the sulfonated silica supporter. This result means that the sulfonic acid functional group on the support material (SiO2 –SO3 H) enhances proton conduction in the catalyst layer. Therefore, the ohmic resistance is decrease in the unit cell. Hence, the sulfonated silica-supported Pt electrocatalyst is a bifunctional electrocatalyst candidate that can be used in the operation of a URFC. Highlights: Electrochemical performance of URFC was enhanced by Pt/SiO2 –SO3 H electro-catalyst. Pt/C catalyst was replaced by Pt/SiO2 –SO3 H catalyst for the higher MEA stability. No degradation in the Pt/SiO2 –SO3 H was observed by the use of carbon-free support. Sulfonic acid functional group (−SO3 H) enhanced proton conduction in catalyst layer. The εRT of Pt/SiO2 –SO3 H is higher than that of Pt/C and Pt/SiO2 electrocatalysts.